Additional aspects of the prediction of postmenopausal osteoporosis - I S Zakharov; G I Kolpinskiy; G A Ushakova (IP Berlin A.V., 2015)
The aim of the present work is to optimize the system prediction of osteoporosis in postmenopausal women. In the present study included 224 postmenopausal women aged up to 65 years, which examined the role of a low intake of calcium and vitamin D deficiency in the prediction of postmenopausal osteoporosis. When assessing the prognostic role of these factors method was used binary logistic regression. The area under the ROC-curve (AUC) was for the level of calcium intake - 0.781 (0.648; 0.913) for the concentration of vitamin D in serum - 0.730 (0.618; 0.843). Comprehensive assessment of studied predictors will increase the predictive value of existing models that determine the probability of occurrence of postmenopausal osteoporosis and optimize the prevention of bone loss in women.